(3GdJPjjd hGdJcejd aj TQM GdJSgjds - (3eMeO Hf jhSa Hf Ydj Hf jhSa GHf nMnqjGf GdZQfGWj GdCfOdSj GdLjGfj, GdpqfraRj, CKjQ GdOjf, CHh MjGf , (B745 (3g` s; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3eMeO Hf CMeO GdZRhdj s)
(3ChdgG (B:s
(3HGH GdeYWha YWa GdfSb(B: (3hgh GdeLghd JGHYkG HCMO MQhag hgj GdhGh hGdaGA hKe hMJi hCe hHd hdG s
(3BNQgG (B:s
(3heY gPg GdGMJeGdGJ dG jchf aj GdGSJTgGO HgPG GdHjJ MLI hGddg Gdehab Ke GdLRA GdNGeS jJdhg aj GdPj jdjg s
(3JSgjd GdahGFO hJcejd GdebGUO dGHf eGdc GdWGFj GdLjGfj GdeJhai (B672(3g`s
(3fSNI Yf NW GdeDdas
(3fSNI QGHYIs
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdfMhs